Medwave’S Editorial History, Policies and Guidelines: 1. Description [Historia, Política y Normas de Medwave: 1. Descripción] - Bachelet-Norelli, V (2017)
This article is the first of a series of four editorials that report on Medwave’s policies, including section policies, formal requisites according to article type, and guidelines for reviewers and authors, with special emphasis on publication and research ethics. The journal believes that it is important to publish its policies in the format of editorials in order to facilitate and ensure dissemination to our broader readership. This editorial refers to the history of the journal from foundation onwards, purpose and scope, mission, open access policy, indexation, among other important aspects.Este artículo corresponde a la primera parte de una serie de cuatro editoriales que reportan acerca de las políticas de Medwave, incluyendo las políticas de secciones, los aspectos formales según tipo de trabajo y las orientaciones generales para autores y revisores, poniendo especial énfasis en la ética de las publicaciones y de la investigación. La revista considera que es importante publicar sus políticas como editoriales para asegurar su debida difusión entre nuestros lectores. El presente editorial se refiere a la historia de la revista, desde su fundación en adelante, a su propósito, misión, política de acceso abierto, indización, entre otros aspectos importantes.